(untitled) (LACCEI, 2024)
The International Program for Scientific Initiation (PI2C) is an activity that was implemented within the scope of the COIL methodology. Created and developed by the Universidad Católica San Pablo (UCSP), in Peru it was carried out collaboratively between professors and engineering students from different Latin American universities and sought to promote the interest of future engineers in research hand in hand with the promotion of intercultural skills.